Sindikat kot predlagatelj v postopku za oceno ustavnosti - Zore, Lea (Delavci in delodajalci, 2014)
According to the Constitutional Court Act, trade unions may under certain conditions (their representativeness or when workers' rights are at risk) require an assessment of constitutionality and legality of regulations and general acts for exercising public mandate. A review of the decisions of the Constitutional Court in cases initiated by the trade unions in the past few years shows that the vast majority of their applications was not substantively addressed; most of the procedures concluded with the decision to reject the application. The aim of this paper is to present recent constitutional case law in this area. A question arising here is whether more cases initiated by the trade unions could get/receive a substantive treatment by greater contribution of the unions themselves, or the reasons for the rejection of cases lies in a stricter interpretation of the legal requirements for filing application to which the unions have no influence.
Keywords: sindikati; ustavna sodišča; ustavnost